More diverse and structurally complex forests are less tightly coupled to ENSO forcing - Pablo Salazar-Zarzosa; Salvador Arenas-Castro; Cristina C. Bastias; David Urquiza Muñoz; Aurelio Diaz Herraiz; Jorge Duran; Yuliana Mendoza; Anke Jentsch; Peter Wolff; Antonio Velasco; Gaston Cruz; Jose Luis Quero (Remote Sensing Applications: Society and Environment, 2026)

Corrigendum to “ENSO-driven distribution shifts in the critically endangered Mustelus whitneyi along the Northern Peruvian Coast” [Mar. Environ. Res. (220) 1-10 108187] - Juliana López-García; Andrés F. Navia; Víctor Hugo Cruz-Escalona; Joanna Alfaro-Shigueto; Jeffrey C. Mangel; Francisco Javier Urcádiz-Cázares; Carlos Yáñez-Arenas (Marine Environmental Research, 2026)

ENSO-driven distribution shifts in the critically endangered Mustelus whitneyi along the Northern Peruvian Coast - Juliana López-García; Andrés F. Navia; Víctor Hugo Cruz-Escalona; Joanna Alfaro-Shigueto; Jeffrey C. Mangel; Francisco Javier Urcádiz-Cázares; Carlos Yáñez-Arenas (Marine Environmental Research, 2026)

Consensus on future research directions in the phylum Rotifera - Rafael L. Macêdo; Carlota Solano‐Udina; Melanie D. Borup; Marco Antonio Jiménez‐Santos; Cristina Arenas‐Sánchez; Christina W. C. Branco; Karen Costa; Betina Kozlowsky‐Suzuki; Cláudia C. Bonecker; Elizabeth J. Walsh; André R. S. Garraffoni; S. S. S. Sarma; et al. (Limnology and Oceanography, 2026)
Rotifers play key roles in aquatic ecosystems, yet significant uncertainty remains about their diversity and evolution, and further evidence is needed to determine how reliably their responses to global change and human impacts can inform conservation. To identify major knowledge gaps hindering progress, we carried out a Delphi process both online and during the 17 th International Rotifer Symposium, involving more than 40 experts across diverse regions and subdisciplines. A total of 133 research questions were screened for relevance and clarity and reduced to 100 for online scoring. These were evaluated on a 1‐to‐10 priority scale, after which 67 questions exceeding 50% agreement were advanced to an in‐person workshop. Through structured discussions and round‐table voting, participants identified gold, silver, and bronze priority questions, while considering the feasibility of addressing them, resulting in a final consensus set of high‐priority questions across basic, applied, and philosophical perspectives including how rotifer communities are defined, how evidence is generated and integrated, and how values shape research priorities. Support for questions on knowledge transfer, digital curation, and AI‐assisted identification highlights the emergence of a methodological subfield linking classical approaches with modern computational tools. Likewise, the emphasis on improving genetic markers and connecting DNA sequences with traits shows that molecular research is now viewed as a foundational component of rotiferology. This synthesis provides the first community‐driven roadmap for rotifer research. By articulating shared priorities and clarifying persistent knowledge gaps, including unreliable phylogenies, uneven sampling worldwide, and limited hypothesis‐driven work, it provides a foundation for future collaborative projects, funding strategies, and cross‐disciplinary integration.

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Iron-rich natural mineral waste enabling the photocatalytic activation of peroxymonosulfate for the oxidation of Enterococcus faecalis and tetracycline - C. Gaye; P. García-Muñoz; J. Vazquez-Arenas; U.M. García-Pérez; J. Rodríguez-Chueca (Chemical Engineering Journal, 2026)

Double-Velocity Anisotropic Rock Physics Templates (DV-ARPT) for analyzing anisotropy in clay-rich rocks using the Maxwell model - Ricardo Ortega-Arenas; Carlos J.T. Nieto-Rivero; Oscar C. Valdiviezo-Mijangos; Rubén Nicolás-López; José A. España-Pinto (Journal of Applied Geophysics, 2026)

Ecotrends: an R package for estimating habitat suitability trends over time - Neftalí Sillero; João Alírio; Nuno Garcia; Inês Freitas; João C. Campos; Lia Bárbara Duarte; Isabel Pôças; Ana Cláudia Teodoro; Salvador Arenas-Castro; A.Márcia Barbosa (Ecological Modelling, 2026)

Time-Series Niche Modelling Reveals Declining Tendencies of Habitat Suitability and Ecological Functions in a Mountainous Protected Area - Inês Freitas; João Alírio; Nuno Garcia; João C. Campos; Salvador Arenas-Castro; Isabel Pôças; Lia Duarte; Ana C. Teodoro; Neftalí Sillero (Environmental Management, 2026)
Monitoring biodiversity in protected areas is essential to mitigate biodiversity loss and evaluate the effectiveness of conservation policies. Integrating satellite remote sensing technologies, ecological niche models, and time-series analyses of biodiversity trends offers a fast and robust approach for assessing habitat suitability changes and species vulnerability over time. In this study, we implemented a framework combining these tools to monitor biodiversity in the Montesinho/Nogueira Special Conservation Area (Northeast Portugal). Using the MaxEnt algorithm, we generated ecological niche models for 342 species based on a time series (2001–2023) of remote sensing data from the Moderate-Resolution Imaging Spectroradiometer (MODIS) sensor. We analysed habitat suitability trends with the Mann-Kendall test to detect changes in habitat quality, as a metric of species vulnerability for individual species, five major taxonomic groups (vascular flora, amphibians, reptiles, birds, and mammals), functional groups (e.g. climate affinity, habitat type, diet, activity, reproduction), and conservation status (regional and European levels). Our study revealed a significant decline in habitat suitability over the past two decades, impacting all taxonomic groups and ecological functions. We observed a high variability in habitat suitability trends among species and taxonomic/functional groups, highlighting the complexity of biodiversity responses to environmental changes. Functional traits such as climatic affinity, trophic level or habitat specialisation were associated with variable rates of habitat decline, with species of Atlantic affinity, species associated with croplands and wetlands, and species specialised in insectivorous diets being at higher risk. Overall, these findings emphasise the need for comprehensive biodiversity monitoring programmes and demonstrate the utility of our approach to inform evidence-based conservation strategies in protected areas globally.

When Good Fit Goes Bad: Identifying and Minimising Overfitting in Ecological Niche Models - Diana Sousa‐Guedes; A. Márcia Barbosa; Salvador Arenas‐Castro; João C. Campos; Neftalí Sillero (Journal of Biogeography, 2026)
Aim To synthesise current understanding of overfitting as a pervasive and often underdiagnosed problem in correlative ecological niche models (ENMs), and to assess its consequences for model interpretation, generalisation and transferability under contemporary data and methodological practices. Location Worldwide. Methods We reviewed the ENM literature, synthesising theoretical and empirical studies that address the detection and treatment of overfitting. We examined diagnostic approaches, including spatially and environmentally structured cross‐validation, and evaluated modelling practices related to sampling bias, predictor choice, study area definition, model complexity and regularisation. Results Common warning signs of overfitting include large discrepancies between training and testing performance, fragmented or ecologically implausible prediction maps and unrealistic response curves. Spatially and environmentally structured cross‐validation approaches are effective for assessing data independence and diagnosing inflated performance estimates. Although multiple mitigation strategies can reduce overfitting, the persistent lack of generalisation often reflects limitations related to data quality, spatial and environmental scale, and violated ecological assumptions rather than modelling choices alone. Main Conclusions Predictive accuracy alone is insufficient for evaluating correlative ENMs. Ecological plausibility, interpretability and consistency with known species distributions are equally important for assessing model reliability. We advocate for iterative model evaluation, explicit consideration of ecological assumptions, and transparent reporting as best practices to improve the trustworthiness and transferability of ENMs in ecological research and conservation planning.

Hybrid Projections Improve Prediction of Distributional Shifts of Invasive and Native Seaweeds Under Climate Change - Sandra Hernández; Francisco Arenas; Ines Haberle; Laura Rodríguez; Francisco Carreño; Brezo D. C. Martínez (Journal of Biogeography, 2026)
Aim Using correlative species distribution models (SDMs) to predict species' range shifts may have limited predictive power when extrapolating into climatic conditions outside those used to train the models. The inclusion of physiological responses to add mechanistic knowledge can increase the reliability of predictions, but it is seldom applied. The objective of this study was to demonstrate this approach with two coexisting and potentially competing macroalgae in Europe and North America—the native Chondrus crispus and the invasive Grateloupia turuturu— and discuss the implications in broader biological and ecological contexts. Location Worldwide. Time Period 2000–2014 and 2090–2100. Major Taxa Studied Marine macroalgae. Methods We (i) developed SDMs from distributional records aiming to represent the realised niche of C. crispus and G . turuturu ; (ii) provided an experimental proxy of thermal fundamental niche by determining growth and survival thermal physiological thresholds (PTs), using it to project the worldwide distribution of the selected macroalgae; and (iii) combined both approaches into a hybrid one derived from the SDM habitat suitability projections post‐filtered with the PTs excluding thermally unsuitable areas. Results Hybrid projections detected and corrected extrapolations of SDMs in areas outside the fundamental niche of thermal tolerance of species, with greater restrictions for the native C. crispus due to its lower upper thermal PT compared to the invasive G . turuturu . Both species are expected to experience future distribution changes and move towards the poles. However, because the invasive species presents a wider thermal niche unfilling state, its potential northward range shift at southern latitudes in the Northern Hemisphere will be smaller. Main Conclusions Habitat suitability projections were more realistic and complete with the correction of the SDMs with the PTs into hybrid projections than those obtained from the two approaches independently and could provide an early warning of the potential replacement of the native species by the invasive one at the contracting limits of distribution.

The combination of hyaluronic acids and collagen boosts human Achilles tendon-derived cell escape from inflammation and matrix remodeling in vitro - Noemi Mencarelli; Dora Arena; Marida Salamone; Laura Pietrangelo; Anna C. Berardi; Amelia Cataldi; Simone Carradori; Marialucia Gallorini (Inflammation Research, 2025)

Photocatalytic disinfection of wastewater using peroxymonosulfate activated by pyrite, chalcopyrite and marcasite under solar irradiation - C. Gaye; P. García-Muñoz; J. Vazquez-Arenas; R.H. Lara; J. Rodríguez-Chueca (Chemical Engineering Journal, 2025)

Is a warmer environment better for a high-mountain lizard? - Mirna C. Vera-Chávez; Donald B. Miles; Diego M. Arenas-Moreno; Fausto R. Méndez-de la Cruz (Journal of Thermal Biology, 2025)

Ni-based catalysts for green H2 production from valorized components of spent NiMH batteries - Karina P. de la Cruz; Issis C. Romero-Ibarra; Angel E. Yañez-Rios; Luis Lartundo-Rojas; Gabriel Trejo; Jorge Vazquez-Arenas (Journal of Environmental Chemical Engineering, 2025)

RuO2-X (X=Bi3O11Ru3, Co3O4, Mn3O4)/Ti electrocatalysts producing HOCl for pharmaceuticals degradation using an advanced UV254 photo-assisted electrochemical process - Angel E. Yañez-Rios; Beatriz Bonola; Roberto L. Palomino-Resendiz; Arturo Manzo-Robledo; Issis C. Romero-Ibarra; Ricardo E. Palma-Goyes; Jorge Vazquez-Arenas (Journal of Environmental Chemical Engineering, 2025)

Metagenomic analysis reveals environmental drivers of Actinobacteriota-associated antibiotic resistance and biosynthetic genes in colombian caribbean resource islands - Liliana Camargo-Montoya; Leslie Leal-Mejia; Nelson Enrique Arenas; Diego C. Franco; Nelson Valero-Valero; Javier Vanegas (Journal of Arid Environments, 2025)

Evaluating the capability of tannic acid-modified biochar in sequestering metal ions and in enhancing soil health - L. Santorufo; G. Maglione; G. Costanzo; G. De Tommaso; F. De Paola; G. Roviello; E. Chianese; C. Ferone; F. Polimeno; M. Riccardi; G. Maisto; M. Iuliano; et al. (International Journal of Environmental Science and Technology, 2025)
Pollution of soils is one of the currently significant environmental concerns. Heavy metals that contaminate the soil can have harmful effects on crops, enter the food chain, and pose a threat to human health. Various approaches have been employed in the past to remediate heavy metal-contaminated soils for agricultural use, including the use of biochar and its modified forms through physical or chemical methods. In the present study, the suitability of tannic acid as a biochar modifier was evaluated for the first time with the aim of enhancing its ability to adsorb Cd and Pb, thereby reducing their transfer from soil to plants. A mesocosm trial was set-up using three treatments: control, unmodified biochar, and tannic acid-modified biochar and their impact was evaluated on soil characteristics and plant physiology. The FT-IR spectra demonstrate that tannic acid-modified biochar considerably improved its capability to absorb Cd but worsened those for Pb and this occurred due to an increase in oxygen-containing functional groups and a reduction in total pore volume, respectively. Tannic acid-modified biochar application increased the carbon and nitrogen concentrations in the soil, as well as the microbial biomass and activities. Lettuce plants grown on soil amended with modified biochar accumulated a low Cd amount in roots but a high Pb amount in leaves that reduced the photosynthetic pigments and the photosynthetic rates and increased the antioxidant response. It is found that tannic acid treatment of biochar is effective for the remediation of Cd-contaminated soils but not for those polluted by Pb.

On land record of the Oligocene–Miocene transition. Climatic insights from a multiproxy study on a lacustrine system in the Ebro Basin (NE Iberia, SW Europe) - C. Arenas; L. Cabrera; M.C. Osácar; F.J. Pérez-Rivarés; L. Valero; J. Bastida (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

High-resolution multi-technique analysis of a continuous sediment core of the Baza Formation at Barranco León (Guadix-Baza Basin, Granada): First petrophysical results - A. Santamaría Barragán; J. M. Parés; S. Colino García; A. Churruca Clemente; T. Fujioka; A. Serrano-Ramos; M. B. Toffolo; A. Alvaro Gallo; M. del Val; J. Iglesias-Cibanal; J. Jáimez; L. Miguens; et al. (Journal of Iberian Geology, 2025)

Diverse ecological responses of foraminifera to the Middle Eocene Climatic Optimum (MECO) in shallow-water settings (Provençal Domain, NW Italy) - A. Gandolfi; V.M. Giraldo-Gómez; L. Arena; V. Luciani; C.A. Papazzoni; J. Pignatti; M. Piazza; L. Kocsis; C. Baumgartner; A. Briguglio (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Assessing spatial and temporal trends over time in potential species richness using satellite time-series and ecological niche models - Nuno Garcia; João C. Campos; João Alírio; Lia B. Duarte; Salvador Arenas-Castro; Isabel Pôças; Ana C. Teodoro; Neftalí Sillero (Biodiversity and Conservation, 2025)
Assessing biodiversity in protected areas is essential for effective conservation management. However, conventional methods for estimating species richness can lead to inaccurate assessments of biodiversity in these regions. To address this, we present a complementary approach to assess potential species richness at a 1 km resolution in the special conservation area of Montesinho/Nogueira (SAC-MN; Portugal), based on a spatial and temporal estimates of species richness trends over time (2001–2021). We compiled 10,190 species occurrence records from four taxonomic groups: amphibians, reptiles, birds, and mammals. We created correlative ecological niche models (MaxEnt) with a time series of satellite-remote sensing variables (SRS-ENMs) using Google Earth Engine (GEE). We calculated annual potential species richness (PSR) maps by stacking the SRS-ENMs and identified positive and negative trends with the Mann–Kendall test. Each species’ ecological niche model revealed unique patterns of habitat suitability within SAC-MN over time. The eastern and western boundaries of SAC-MN revealed an increase in PSR, while the central area indicated PSR declines. Each group displayed different trends in PSR: birds and mammals were more similar between them than amphibians and reptiles. This approach provides ecologists and conservationists with valuable tools to evaluate PSR and trends over time, offering crucial insights for decision-makers and stakeholders to support local biodiversity conservation efforts.

Testing molecular date estimates using an ecological and vicariant case study in treefrogs: The Geological‐Ecological Molecular Calibration - Michael J. Jowers; Jesús Muñoz Pajares; John Weber; Jeanette Arkle; Salvador Arenas‐Castro; Simon Y. W. Ho; Gilson A. Rivas; John C. Murphy; Amaël Borzée; R. Alexander Pyron; Marcos Perez‐Losada; Mayke De Freitas; et al. (Journal of Biogeography, 2024)
Aim To date a vicariant event through the mutualistic relationship of a hylid frog and its bromeliad host found across two isolated mountain ranges as part of an island–continental split and to use this information to calibrate a molecular dating analysis of hylids. Location South America. Time Period Pliocene. Major Taxa Studied Treefrogs, Arboranae. Methods Pliocene tectonic movements sank a portion of a mountain range that connected present‐day Trinidad (island) and northern Venezuela, eventually isolating populations of the golden tree frog Phytotriades auratus and its host bromeliad Glomeropitcairnia erectiflora on both sides of a saltwater barrier. We estimated the submersion rate timing of the vicariant event, then employed ecological niche modelling to establish the distribution of the frog and its host to the Pliocene. We generated nucleotide sequence data for the hylid on each side of the marine barrier and proposed a biogeographic calibration for the split between populations. Using Bayesian phylogenetic analysis, we evaluated the impact of incorporating this biogeographic calibration on estimates of treefrog divergence times. Results A relatively continuous, high‐elevation mountain range existed before the Pliocene and the opening of the Gulf of Paria (4.45 ± 0.85 Ma). Phytotriades auratus and G. erectiflora would have been distributed across the Paria and Northern Range mountains as a single population since the Pliocene. Divergence times among treefrogs (Arboranae) were older than those inferred using fossil calibrations alone, with mean age estimates for subfamilies and genera being ~2 and ~1.2 million years older, respectively. Main Conclusions Our study presents a biogeographic calibration based on a vicariant model that connects the evolution of the populations of a hylid through geology and ecological data. The implementation of this date as a molecular clock calibration reduces the uncertainty in date estimates for the shallower nodes in the phylogeny of Arboranae.

Modeling the effects of pore aspect ratio, porosity, and seismic anisotropy on wave velocity dispersion and attenuation patterns in oil- and brine-saturated carbonates using a dynamic self-consistent anisotropic approach - Ricardo Ortega-Arenas; Jaime Meléndez-Martínez; Rubén Nicolás-López; Oscar C. Valdiviezo-Mijangos; Federico J. Sabina (Acta Geophysica, 2024)

European Network for Optimization of Veterinary Antimicrobial Therapy (ENOVAT) guidelines for antimicrobial use in canine acute diarrhoea - L.R. Jessen; M. Werner; D. Singleton; C. Prior; F. Foroutan; A.A. Ferran; C. Arenas; C. R. Bjørnvad; E. Lavy; F. Allerton; K. Allensbach; L. Guardabassi; et al. (The Veterinary Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P20-10 Embracing regulatory compliance: Genetox meets generation SEND - S. Salazar Arenas; C. Bapat; M. Ellison; M. Wasko; F. Hall (Toxicology Letters, 2024)

Dynamic shifts of functional diversity through climate-resilient strategies and farmland restoration in a mountain protected area - João C. Campos; João Alírio; Salvador Arenas-Castro; Lia Duarte; Nuno Garcia; Adrián Regos; Isabel Pôças; Ana C. Teodoro; Neftalí Sillero (Journal of Environmental Management, 2024)

A low dose of benzo(a)pyrene during prepuberty in male rats generated immediate oxidative stress in the testes and compromised steroidogenic enzymes/proteins - Bárbara C. Jorge; Ana C.C. Reis; Julia Stein; Beatriz R. Paschoalini; Jéssica N. Bueno; Suyane da Silva Moreira; Alana R. Godoi; Vanessa C. Fioravante; Francisco E. Martinez; Patrícia F.F. Pinheiro; Arielle C. Arena (Reproductive Toxicology, 2024)

Artificial Light at Night Reduces Flashing in Photinus and Photuris Fireflies During Courtship and Predation - Juan S. Hillón-Salas; Juan D. Pineda-Dueñas; Ana M. Romero-Chacón; Juliana Fonseca-Tellez; Manuela Cardona-Restrepo; Sofía C. Garrido-Villegas; Diego Mejía-Tovar; Camilo Arenas-Ríos; Laia Gaitán-Botero; Zulma S. Barón-Garzón; Andrés F. Robayo-Salek; Harold Pulido-Guarín; et al. (Journal of Insect Behavior, 2024)
Artificial light at night (ALAN) affects species-specific communication in a wide range of nocturnal species, including fireflies (Lampyridae). Fireflies rely on bioluminescent signals for communicating. In this study, we conducted two manipulative field experiments to evaluate the effect of artificial light at night on the flashing activity of male and female neotropical fireflies during courtship and predation. Our results showed a significant reduction in the flashing activity of both males and females exposed to ALAN during courtship and predation. Remarkably, the effect of ALAN on male flashing activity seems to be independent of female flashing activity. In conclusion, ALAN disrupts bioluminescent intraspecific (courtship) and interspecific (predation) communication, which in turn could influence mating success, thus negatively affecting neotropical firefly populations in the long term. Our findings contribute to understanding the challenges faced by neotropical firefly communities in the presence of ALAN.

Efficacy of antimicrobial and nutraceutical treatment for canine acute diarrhoea: A systematic review and meta-analysis for European Network for Optimization of Antimicrobial Therapy (ENOVAT) guidelines - K. Scahill; L.R. Jessen; C. Prior; D. Singleton; F. Foroutan; A.A. Ferran; C. Arenas; C.R. Bjørnvad; E. Lavy; F. Allerton; J.S. Weese; K. Allenspach; et al. (The Veterinary Journal, 2024)

Testing the record of climate-related cyclicity in microbial lamination: An example from Miocene oncolites in the Ebro Basin, Spain - F.J. Pérez-Rivarés; G. Pardo; C. Arenas (Sedimentary Geology, 2024)

Exposure to ambient air toxicants and the risk of amyotrophic lateral sclerosis (ALS): A matched case control study - Fan Wu; Angela M. Malek; Jeanine M. Buchanich; Vincent C. Arena; Judith R. Rager; Ravi K. Sharma; John E. Vena; Todd Bear; Evelyn O. Talbott (Environmental Research, 2024)

Understanding different dominance patterns in western Amazonian forests - Laura Matas‐Granados; Frederick C. Draper; Luis Cayuela; Julia G. de Aledo; Gabriel Arellano; Celina Ben Saadi; Timothy R. Baker; Oliver L. Phillips; Eurídice N. Honorio Coronado; Kalle Ruokolainen; Roosevelt García‐Villacorta; Katherine H. Roucoux; et al. (Ecology Letters, 2024)
Dominance of neotropical tree communities by a few species is widely documented, but dominant trees show a variety of distributional patterns still poorly understood. Here, we used 503 forest inventory plots (93,719 individuals ≥2.5 cm diameter, 2609 species) to explore the relationships between local abundance, regional frequency and spatial aggregation of dominant species in four main habitat types in western Amazonia. Although the abundance‐occupancy relationship is positive for the full dataset, we found that among dominant Amazonian tree species, there is a strong negative relationship between local abundance and regional frequency and/or spatial aggregation across habitat types. Our findings suggest an ecological trade‐off whereby dominant species can be locally abundant ( local dominants ) or regionally widespread ( widespread dominants ), but rarely both ( oligarchs ). Given the importance of dominant species as drivers of diversity and ecosystem functioning, unravelling different dominance patterns is a research priority to direct conservation efforts in Amazonian forests.

Combined effects of climate change and environmentally relevant mixtures of endocrine disrupting compounds on the fitness and gonads' maturation dynamics of Nucella lapillus (Gastropoda) - H. Morais; F. Arenas; C. Cruzeiro; S. Galante-Oliveira; P.G. Cardoso (Marine Pollution Bulletin, 2023)

Range‐edge populations of seaweeds show niche unfilling and poor adaptation to increased temperatures - Sandra Hernández; Ana G. García; Francisco Arenas; M. Pilar Escribano; Alexander Jueterbock; Olivier De Clerck; Christine A. Maggs; João N. Franco; Brezo D. C. Martínez (Journal of Biogeography, 2023)
Aim Global warming is affecting the distribution of species worldwide, but the level of adaptation of edge populations to warmer temperatures remains an open question. Here, we assess the thermal tolerance of populations of two habitat‐forming seaweeds along their latitudinal range, using thermal niche unfilling to assess their resilience to global warming. Location European Atlantic coastline. Taxon Ascophyllum nodosum (Linnaeus) Le Jolis (Phaeophyceae) and Chondrus crispus Stackhouse (Rhodophyta). Methods We studied the ecotypic variation in upper survival temperatures (USTs) by measuring survival and growth of adults representing populations under a gradient of seawater temperature (12–30°C). Comparing the USTs with maximum seawater temperatures obtained from satellites, we investigated safety margins and niche unfilling states, both in recent history and under future climate scenarios. Results USTs (≈24°C) did not differ significantly between populations, except for higher values (27.9°C) for the northernmost populations (cold edge) of A . nodosum . Populations of both species had thermal safety margins over the last few decades (from 1982 to 2021). However, projections based on USTs showed that in several years these margins have been eliminated and will completely disappear in the Bay of Biscay under RCP4.5 and RCP6.0 2090–2100 IPCC scenarios for C . crispus and under RCP8.5 for both species, threatening the populations there. Main Conclusions Southern marginal populations were not better adapted to global warming than populations elsewhere. Both seaweed species tolerated higher temperatures than the ambient maxima, suggesting a thermal niche unfilling state with thermal safety margins in their recent history. However, those are being depleted by ongoing climate change and this trend is predicted to increase. Marine heat waves are important threats to these habitat‐forming species, transiently reducing or even eliminating safety margins in the hottest parts of the European Atlantic coastline, contributing to explaining the distributional gap there.

Long-term air pollution and risk of amyotrophic lateral sclerosis mortality in the Women's Health Initiative cohort - Angela M. Malek; Vincent C. Arena; Ruopu Song; Eric A. Whitsel; Judith R. Rager; James Stewart; Jeff D. Yanosky; Duanping Liao; Evelyn O. Talbott (Environmental Research, 2023)

VIGIRISKS platform, a web-tool for single and multi-hazard risk assessment - C. Negulescu; F. Smai; R. Quique; A. Hohmann; U. Clain; R. Guidez; A. Tellez-Arenas; A. Quentin; G. Grandjean (Natural Hazards, 2023)
Enabling storing, scenario design, documentation, access and execution of scientific computations for multirisks mapping is the aim of the VIGIRISKS web platform currently designed and developed by the BRGM (French Geological Survey). VIGIRISKS platform insures geohazards data management, reproducibility of risks calculations, allows information transparency and improving efficiency by easing collaborative work and sharing results and practices. The scientific scope is multirisk mapping, including cascading effects, in the domain of natural hazard (earthquake, landslide and submersion) from the phenomenon modelling to the impact evaluation on exposed elements such as buildings. VIGIRISKS web platform initially designed for BRGM experts aims to be in a long-term an open repository for national and international experts working on natural hazards management. Integration and deployment of new datasets and computational processes oriented towards risks mapping is as automatic as possible for the convenience of users.

The inverse autotransporters of Yersinia ruckeri , YrInv and YrIlm , contribute to biofilm formation and virulence - Agnieszka Wrobel; Athanasios Saragliadis; Jesús Pérez‐Ortega; Carolin Sittman; Stephan Göttig; Krystyna Liskiewicz; Maria Helle Spence; Kenneth Schneider; Jack C. Leo; Jesús Arenas; Dirk Linke (Environmental Microbiology, 2020)
Summary Yersinia ruckeri causes enteric redmouth disease (ERM) that mainly affects salmonid fishes and leads to significant economic losses in the aquaculture industry. An increasing number of outbreaks and the lack of effective vaccines against some serotypes necessitates novel measures to control ERM. Importantly, Y. ruckeri survives in the environment for long periods, presumably by forming biofilms. How the pathogen forms biofilms and which molecular factors are involved in this process, remains unclear. Yersinia ruckeri produces two surface‐exposed adhesins, belonging to the inverse autotransporters (IATs), called Y. ruckeri invasin (YrInv) and Y. ruckeri invasin‐like molecule (YrIlm). Here, we investigated whether YrInv and YrIlm play a role in biofilm formation and virulence. Functional assays revealed that YrInv and YrIlm promote biofilm formation on different abiotic substrates. Confocal microscopy revealed that they are involved in microcolony interaction and formation, respectively. The effect of both IATs on biofilm formation correlated with the presence of different biopolymers in the biofilm matrix, including extracellular DNA, RNA and proteins. Moreover, YrInv and YrIlm contributed to virulence in the Galleria mellonella infection model. Taken together, we propose that both IATs are possible targets for the development of novel diagnostic and preventative strategies to control ERM.

The antioxidant power of horseradish, Armoracia rusticana , underlies antimicrobial and antiradical effects, exerted in vitro - Simona Manuguerra; Letteria Caccamo; Monique Mancuso; Rosaria Arena; Alessandro C. Rappazzo; Lucrezia Genovese; Andrea Santulli; Concetta M. Messina; G. Maricchiolo (Natural Product Research, 2020)

A morphological, reproductive, and molt phenology database for 379 bird species from the Colombian Tropical Andes - Leydy J. Cardona‐Salazar; Yeny A. Benavides‐Ossa; Ángela M. Vargas‐Daza; Juan F. Betancurt‐Grisales; Mauricio Bohada‐Murillo; Estefani T. Martínez‐Sánchez; Marelid Cardona‐Romero; Ana Busi; William D. Tobón‐Escobar; Mateo Ortíz‐Giraldo; Daniela Gómez Castillo; Johnathan Alvarez‐Londoño; et al. (Ecology, 2020)
The Colombian Tropical Andes are one of the regions with highest bird diversity on Earth. However, information on bird morphology, reproductive phenology, and molt is particularly scarce in this region. Also, this region is heavily impacted by deforestation, and it is vulnerable to climate change. Hence, providing baseline information on life history and morphological traits will be essential to support future research on functional diversity, climate change effects, conservation, evolution, and phenology. To fill this gap, we have compiled information on bird distribution, morphology, molt, and reproductive phenology at 52 localities of the Department of Caldas, covering an elevation range between 148 and 3845 m. This compilation comprises a wide range of habitats, including native forests, forestry plantations, croplands, and paramo. Our database presents information for 3,398 records belonging to 379 bird species (representing 23 orders, 53 families, and 258 genera). From those records, 2,843 correspond to information collected in the field between 2008 and 2019, and the remaining 555 records correspond to specimens deposited in the Natural History Museum of the Caldas University, collected between 1969 and 2014. We measured nine morphological traits from all specimens: total culmen, gape, bill width, bill depth, tarsus, wing length, tail length, total length, and mass. We also have reproductive condition information for 257 species and molt information available for 378 species. The information contained in this data set represents ~20% of the Colombian avifauna and ~11% of the bird species richness in South America. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Antidiabetic, cytotoxic and antioxidant activities of oil extracted from Acrocomia aculeata pulp - Perla V. B. da Silva; Marianne M. Ramiro; Edna K. K. Iriguchi; William A. Corrêa; Jennifer Lowe; Claudia A. L. Cardoso; Arielle C. Arena; Cândida A. L. Kassuya; Rozanna M. Muzzi (Natural Product Research, 2019)

Baseline prepulse inhibition of the startle reflex predicts the sensitivity to the conditioned rewarding effects of cocaine in male and female mice - M. C. Arenas; C. I. Navarro-Francés; S. Montagud-Romero; J. Miñarro; C. Manzanedo (Psychopharmacology, 2018)

Cistus monspeliensis L. as a potential species for rehabilitation of soils with multielemental contamination under Mediterranean conditions - Daniel Arenas-Lago; Erika S. Santos; Luisa C. Carvalho; Maria Manuela Abreu; Maria Luisa Andrade (Environmental Science and Pollution Research, 2018)

On time-domain uncoupled analyses for offshore wind turbines under seismic loads - F. Santangelo; G. Failla; F. Arena; C. Ruzzo (Bulletin of Earthquake Engineering, 2018)

Seroprevalence and risk factors associated with Brucella seropositivity in dairy and mixed cattle herds from Ecuador - A. Carbonero; L.T. Guzmán; I. García-Bocanegra; C. Borge; L. Adaszek; A. Arenas; L. R. Saa (Tropical Animal Health and Production, 2018)

Consumption and feeding preference of Paracentrotus lividus (Echinodermata: Echinoidea) on native and non-native macroalgae from northern west coast of Iberia - André C. Cardoso; João N. Franco; João N. Franco; João N. Franco; João N. Franco; Isabel Sousa-Pinto; Francisco Arenas (Frontiers in Marine Science, 2018)

Estimation of tile drainage contribution to streamflow and nutrient loads at the watershed scale based on continuously monitored data - A. Arenas Amado; K. E. Schilling; C. S. Jones; N. Thomas; L. J. Weber (Environmental Monitoring and Assessment, 2017)

Self‐fertilization, long‐distance flash invasion and biogeography shape the population structure of Pseudosuccinea columella at the worldwide scale - M. Lounnas; A. C. Correa; A. A. Vázquez; A. Dia; J. S. Escobar; A. Nicot; J. Arenas; R. Ayaqui; M. P. Dubois; T. Gimenez; A. Gutiérrez; C. González‐Ramírez; et al. (Molecular Ecology, 2017)
Population genetic studies are efficient for inferring the invasion history based on a comparison of native and invasive populations, especially when conducted at species scale. An expected outcome in invasive populations is variability loss, and this is especially true in self‐fertilizing species. We here focus on the self‐fertilizing Pseudosuccinea columella , an invasive hermaphroditic freshwater snail that has greatly expanded its geographic distribution and that acts as intermediate host of Fasciola hepatica , the causative agent of human and veterinary fasciolosis. We evaluated the distribution of genetic diversity at the largest geographic scale analysed to date in this species by surveying 80 populations collected during 16 years from 14 countries, using eight nuclear microsatellites and two mitochondrial genes. As expected, populations from North America, the putative origin area, were strongly structured by selfing and history and harboured much more genetic variability than invasive populations. We found high selfing rates (when it was possible to infer it), none‐to‐low genetic variability and strong population structure in most invasive populations. Strikingly, we found a unique genotype/haplotype in populations from eight invaded regions sampled all over the world. Moreover, snail populations resistant to infection by the parasite are genetically distinct from susceptible populations. Our results are compatible with repeated introductions in South America and flash worldwide invasion by this unique genotype/haplotype. Our study illustrates the population genetic consequences of biological invasion in a highly selfing species at very large geographic scale. We discuss how such a large‐scale flash invasion may affect the spread of fasciolosis.

Topiramate increases the rewarding properties of cocaine in young-adult mice limiting its clinical usefulness - M. C. Arenas; A. Mateos-García; C. Manzanedo; M. Rodríguez-Arias; M. A. Aguilar; F. Navarrete; M. S. García Gutiérrez; J. Manzanares; J. Miñarro (Psychopharmacology, 2016)

Eco-physiological response to water stress of drought-tolerant and drought-sensitive tomato genotypes - M. M. Rigano; C. Arena; A. Di Matteo; S. Sellitto; L. Frusciante; A. Barone (Plant Biosystems, 2016)

MicroNESS: an innovative opening–closing multinet for under pack-ice zooplankton sampling - L. Guglielmo; G. Arena; C. Brugnano; R. Guglielmo; A. Granata; R. Minutoli; R. Sitran; G. Zagami; A. Bergamasco (Polar Biology, 2015)

Sex differences in the long-lasting consequences of adolescent ethanol exposure for the rewarding effects of cocaine in mice - A Mateos-García; C Manzanedo; M Rodríguez-Arias; M. A. Aguilar; E. Reig-Sanchis; C. I. Navarro-Francés; O. Valverde; J. Miñarro; M. C. Arenas (Psychopharmacology, 2015)

Higher sensitivity to the conditioned rewarding effects of cocaine and MDMA in High-Novelty-Seekers mice exposed to a cocaine binge during adolescence - A. Mateos-García; C. Roger-Sánchez; M. Rodriguez-Arias; J. Miñarro; M. A. Aguilar; C. Manzanedo; M. C. Arenas (Psychopharmacology, 2015)

The regime of climate-related disturbance and nutrient enrichment modulate macroalgal invasions in rockpools - Iacopo Bertocci; J. Domínguez Godino; C. Freitas; M. Incera; R. Araújo; A. Bio; F. Arenas; I. Sousa-Pinto; P. A. Reis; R. Domínguez (Biological Invasions, 2015)

Morphological and physiological modifications of Cistus salvifolius L. winter leaves in response to the rise in winter temperatures - L. Vitale; V. Magliulo; C. Arena (Plant Biosystems, 2014)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

Tellurite reduction by Escherichia coli NDH-II dehydrogenase results in superoxide production in membranes of toxicant-exposed cells - Waldo A. Díaz-Vásquez; María J. Abarca-Lagunas; Felipe A. Arenas; Camilo A. Pinto; Fabián A. Cornejo; Poorna T. Wansapura; Gayan A. Appuhamillage; Thomas G. Chasteen; Claudio C. Vásquez (BioMetals, 2014)

Functional diversity and climate change: effects on the invasibility of macroalgal assemblages - F. Vaz-Pinto; C. Olabarria; I. Gestoso; E. Cacabelos; M. Incera; F. Arenas (Biological Invasions, 2013)

Seasonal changes in photosynthetic activity and photochemical efficiency of the Mediterranean shrub Phillyrea angustifolia L - L. Vitale; C. Arena; A. Virzo De Santo (Plant Biosystems, 2012)

Harmonic amplitude-terms mask to highlight agriculture in the savanna domain below the Brazilian Amazonian frontier - J. M. Arenas-Toledo; J. C. N. Epiphanio (International Journal of Remote Sensing, 2011)

Gas exchange and leaf metabolism of irrigated maize at different growth stages - L. Vitale; C. Arena; P. Carillo; P. Di Tommasi; B. Mesolella; F. Nacca; A. Virzo De Santo; A. Fuggi; V. Magliulo (Plant Biosystems, 2011)

Partial characterization of hepatopancreatic and extracellular digestive proteinases of wild and cultivated Octopus maya - R. Martínez; R. Sántos; A. Álvarez; G. Cuzón; L. Arena; M. Mascaró; C. Pascual; C. Rosas (Aquaculture International, 2011)

PM10 air pollution exposure during pregnancy and term low birth weight in Allegheny County, PA, 1994–2000 - Xiaohui Xu; Ravi K. Sharma; Evelyn O. Talbott; Jeanne V. Zborowski; Judy Rager; Vincent C. Arena; Conrad Dan Volz (International Archives of Occupational and Environmental Health, 2011)

Factors controlling present-day tufa dynamics in the Monasterio de Piedra Natural Park (Iberian Range, Spain): depositional environmental settings, sedimentation rates and hydrochemistry - M. Vázquez-Urbez; C. Arenas; C. Sancho; C. Osácar; L. Auqué; G. Pardo (International Journal of Earth Sciences, 2010)

Establishing physiological blood parameters in the loggerhead sea turtle (Caretta caretta) - D. Gelli; V. Ferrari; A. Zanella; P. Arena; L. Pozzi; S. Nannarelli; C. Vaccaro; D. Bernardini; S. Romagnoli (European Journal of Wildlife Research, 2009)

Does pollen function as a reward for honeybees in associative learning? - C. Grüter; A. Arenas; W. M. Farina (Insectes Sociaux, 2008)

Photosynthesis and photoprotective strategies in Laurus nobilis L. and Quercus ilex L. under summer drought and winter cold - C. Arena; L. Vitale; A. Virzo de Santo (Plant Biosystems, 2008)

Characterization of a Lactobacillus plantarum Strain Able to Produce Tyramine and Partial Cloning of a Putative Tyrosine Decarboxylase Gene - M. E. Arena; D. Fiocco; M. C. Manca de Nadra; I. Pardo; G. Spano (Current Microbiology, 2007)

Effect of melatonin on hyperlipidemic nephropathy under constant light exposure - I. Túnez; M. C. Muñoz; M. Feijoo-López; E. Valdelvira; I. Bujalance-Arenas; P. Montilla (Journal of Physiology and Biochemistry, 2002)

Predicting Starling Chick Carcass PCB Concentrations from PCB Concentrations in Ingested Animal Matter - S. M. Arena; R. S. Halbrook; C. A. Arenal (Archives of Environmental Contamination and Toxicology, 1999)